Characteristics of the Former Salt Factory of Kalianget, Sumenep - Vicelia Intan Savila Savila; Dwita Hadi Rahmi (Built Environment Studies, 2022)
The term of morphology is widely used to describe the physical form of urban areas based on the historical city. The Old City of Kalianget is a modern city that was built as the salt briquette factory area during the colonial period in 1899. This study aims to identify the characteristics of urban morphology in the old city of Kalianget. The deductive qualitative method is used from the beginning of identifying the area problems, field survey and data analysis. This study uses the urban design theory by Roger Trancik. The urban design theory identifies morphology through figure ground analysis, linkage theory, and place theory. The study shows the land was dominated by the factory area in 1947 and has been dominated by the residence and abandoned buildings nowdays. Moreover, the road structure is formed with a grid pattern with the intersections between roads and dominated by T-junction. The center of the old city of Kalianget is an open space in the middle of the area characterized by the plots building. It closes to the open spaces and the main road has the larger size than the next layer.